2020
DOI: 10.1186/s42269-020-00422-9
|View full text |Cite
|
Sign up to set email alerts
|

Albizia chinensis bark extract ameliorates the genotoxic effect of cyclophosphamide

Abstract: Background The genus Albizia (Leguminoseae) is used in folk medicine for the treatment of a wide range of ailments. Recently, saponins from plant origin have attracted much attention. Saponins are recorded to have a broad range of biological and pharmacological activities. This study was performed to evaluate the protective role of Albizia chinensis bark methanolic extract (MEAC) against the genotoxicity induced by cyclophosphamide (CP) using different mutagenic parameters. Results The results showed that ME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Cyclophosphamide is an effective anticancer drug used in the management of many types of cancers, e.g., acute and chronic leukemia, lymphomas, multiple myeloma, breast cancer, ovarian carcinoma, neuroblastoma, and sarcoma (Nabil et al, 2020). It is also used as an immunesuppressant for the treatment of autoimmune diseases (Madondo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Cyclophosphamide is an effective anticancer drug used in the management of many types of cancers, e.g., acute and chronic leukemia, lymphomas, multiple myeloma, breast cancer, ovarian carcinoma, neuroblastoma, and sarcoma (Nabil et al, 2020). It is also used as an immunesuppressant for the treatment of autoimmune diseases (Madondo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The medicinal plants of this species have been reported for hepatoprotective and antioxidant, acetylcholinesterase inhibitory 20, 21, anti-diabetic 22, ant-idiarrheal, antispasmodic, and Bronchodilator effects 23 . A. stipulata is a conventionally significant plant and is reported to possess enormous medicinal properties such as anti-ulcer, anti-proliferative, antioxidant, antidiabetic, anti-microbial and anti-inflammatory, spermicidal, thrombolytic, analgesic, anti-diarrheal, CNS depressant activities of various extract from different parts of the plant and its gum used as a polymer for control released tablets 24,34, which exposed that it has been contained terpenoids, steroids, flavonoids, phenols, saponins, inositol, and quinone. Moreover, previous phytochemical studies revealed the presence of several cytotoxic triterpenes, saponins, glycosides, flavonoids such as luteolin, quercetin, steroids namely Stigmasterol, β-Sitosterol, alkaloids, and phenols 26,35 .…”
mentioning
confidence: 99%